Genes, categories, and species : the evolutionary and cognitive causes of the species problem - Hey, Jody. (Oxford ; New York : Oxford University Press, 2001)
In Genes, Categories and Species, Jody Hey provides an enlightening new solution to one of biology's most ironic and perplexing puzzles. When Darwin showed that life evolves, and that it does so by natural selection, he transformed our understanding of living things. But the very question Darwin addressed-the nature of species-continues to pose an awkward conundrum for biologists. Despite enormous efforts by a great many scholars, biologists still cannot agree on how to identify species or even how to define the word "species." Genes, Categories, and Species is not like other books on the spec.
Foreword; Part I: The Hidden Question; 1. The Species Problem; 2. The Mode of Ignorance; 3. The Theory of Life; Part I: Conclusions; Part II: Species in Nature and within the Mind; 4. Categories; 5. Typological Thinking about Species; 6. Biological Diversity; 7. Recombination and Biological Species; 8. The Cause of the Species Problem; 9. The Origin of Natural Kinds; Part II: Conclusions; Part III: Living with the Species Problem; 10. Phylogeny; 11. Systematics; 12. Evolutionary Biology; 13. What Are Species? What Are Taxa?; 14. What Is to Be Done?; References; Index; A; B; C; D; E.
Includes bibliographical references (pages 195-211).
Print version record.
eBooks on EBSCOhost
Keywords: Species; Espèces (Biologie); SCIENCE -- Life Sciences -- Evolution; Especies; Espèces (Biologie); Species; Species